Penerapan Sistem Jaminan Kesehatan Nasional pada Pelayanan Kebidanan dan Neonatal - Nelly Yuliana; Hendra Setiawan; Nyoman Anita Damayanti (Jurnal Keperawatan Silampari, 2020)
The purpose of this study is to describe the implementation of policies and regulations of the National Health Insurance System in midwifery and neonatal services in X District, North Kalimantan Province. This research method is a qualitative research with an observational descriptive approach. The results of the study show that there are obstacles in the implementation of the national health insurance system, namely the lack of information on national health insurance for midwives and the community and the non-acceptance of non-capitation funds for midwives in the national health insurance system. In conclusion, the national health insurance system still needs a lot of improvements that are still needed for policies and regulations of the national health insurance system both at the central and regional levels, especially in midwifery and neonatal services for midwives so that their implementation can run properly to reduce maternal and child mortality in Indonesia. Keywords: Non-Capitation Fund, Midwifery and Neonatal Services, National Health Insurance System